The Effect of Scaffolding Technique in Teaching Writing of Recount Text at SMK Pembangunan Bukittinggi - Shinta, Novia (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2022)
This   research was   aimed to know the   effect    of    using   scaffolding Technique in teaching writing of recount text at first of SMK Pembangunan. The method used in this research was a quantitative method. To attain the reliability of the test instrument, the researcher used rubric of scoring namely an analytic scoring which was adopted from John Anderson to score the students’ writing on the pre-test and the post-test. To analyze the data the researcher used t-test formula and consulted the result into t-table with the level of significance α = 0.05. The research findings showed that the result of the pre-test and post-test score of the experimental class tₒ (-7,578) was higher than t table (1.717). Hₒ was rejected and Hₐ was accepted. It means that there is a significant effect of using  Scaffolding  Technique  in  teaching  writing  of  recount  text.  Then, the calculation of the post-test both classes: was experimental class and control class, it was obtained that the tₒ (8,307) was higher than the t table () with a degree of freedom  (DF) = 22.  So, the alternative hypothesis (Hₐ) were accepted, which means that there is a significant difference between using scaffolding technique and conventional.  It can be concluded that the hypothesis is accepted. It is proved that using Scaffolding Technique can help the students in improving their ability in writing recount text.